Effective modulation of an aryl acetylenic molecular system based on dithienyldiketopyrrolopyrrole for organic solar cells. Issue 17 (25th January 2016) - Zhang, Chun-Hui; Wang, Li-Ping; Tan, Wan-Yi; Wu, Si-Ping; Liu, Xue-Ping; Yu, Pan-Pan; Huang, Ju; Zhu, Xu-Hui; Wu, Hong-Bin; Zhao, Cun-Yuan; Peng, Junbiao; Cao, Yong
Abstract : Incorporating the 1, 4-phenylene moiety leads to improving the photovoltaic performance. Abstract : We report the synthesis and photovoltaic properties of two conjugated small-molecule acetylenic compounds based on a dithienyldiketopyrrolopyrrole (DT-DPP ) core. In contrast with the parent molecule in which theDT-DPP core and the 9-(1-(3-dodecylthienyl)ethynyl)anthracen-10-yl endgroups are bridged through an acetylenic bond, incorporating a 1, 4-phenylene moiety, connected to the same core and endgroups via the acetylenic linkage, leads to considerably enhanced power conversion efficiency (PCE). Specifically, the lowering of the HOMO level of the resulting compound is supported by DFT calculation of the molecular structures, cyclic voltammetry experiments and increased open-circuit voltage ( V oc ). Moreover, while the lowest-energy absorption maximum is blueshifted, this molecular engineering produces a strong and broad absorption in the visible, as well as a high mobility of 4.50 × 10 −4 cm 2 V −1 s −1, thus contributing to improve the short-circuit current ( J sc ), as evidenced by EQE measurements. The preliminary characterization of the solar cells based on the 1, 4-phenylene engineered compound (ITO/PEDOT:PSS/acetylenic molecular compound:PC61 BM/Al) yielded a PCE of ≈5% with J sc = 9.24 mA cm −2, V oc = 0.87 V, and FF = 63%, which is of considerable significance in view of synthetic accessibility and involving no high-boiling-point solvent additives or solvent vapor annealing, whereas a PCE of 3.86% was obtained for the parent compound with J sc = 8.18 mA cm −2, V oc = 0.73 V, and FF = 64.6%. The present result may provide a simple approach for modulating the electronic properties of organic semiconductors for organic solar cells.